Perancangan Furniture pada Hunian Kost Pekerja di Kawasan Surabaya Timur - Riza Widiatmoko; Adi Santosa (Intra, 2016)
Boarding houses are unarguably most favourite place to stay for settled foreigners. For married couples with children, staying in boarding house means that they are in a very tight budget, usually caused by a high economic demands. When a family stay together in one room, the needs of efficient room facilities are high. One of the needs is furniture, it becomes the focus of the problem towards the complexity of the activities happening faced by the whole-family dwellers. The number of the occupants are too high compared to the space available. This issue then results to the lack of moving space, dirty looking room, and negative health and psychological effect to the user. According to the analysis of the survey data, there are three furniture facilities the user needs, i.e. storage facility, work facility (table/surfaces), and sitting facility (to support the work facility). Then the goal of this design is to integrate those three facilites into one furniture. The designed container cabinet becomes the furniture that fulfills the three facilities in terms of functionality and shape, because this furniture have the ideal dimensions to be transformed and according to survery most of occupants in boarding houses have some kind of furniture that resembles container cabinet. Designed using cheap materials, simple joints, and simple usage mechanism, this furniture will be the right solution to solve the existing problem. A furniture that are compact in size, designed with recycled materials (like rattan, refunction pallet, and coconut timber), and have 3-in-1 functions might just become the right innovation for boarding house space problem.